Speech pathology and linguistics - N, Rathna (Journal of All India Institute of Speech and Hearing, 1971)
The field of Speech and Hearing is a young one in India. The beginnings of organized effort were seen only as recently as eight years ago. Even now there are only a few trained Speech Pathologists and Audiologists—in the country. Actually, some of the trained people are yet to find jobs because posts are only now being created in several places. Except in large cities like Bombay and around the city of Mysore people are not aware of a field such as this; not all people of the medical profession with whom we share a lot of interests are aware of the availability of Speech and Hearing services or of the need for them. With this in mind, I request the indulgence of this seminar while I briefly describe our functions. The intention of this paper is to indicate the kinds of information that linguistics can provide towards the improvement of our professional endeavours. If as a sideline, an impression of how a concern with our field might prove to be of value to the general concerns of linguists is obtained this paper would have been well rewarded.